Resource distribution in disturbed landscapes – the effect of clearcutting on berry abundance and their use by brown bears - Domevscik, Matej (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
To survive winter hibernation, brown bears (Ursus arctos) need to store excess energy during late summer and autumn. Scandinavian brown bears usually have an abundance of berries to feed on, but their distribution varies depending on forest structure and age. Especially on newly cut clearcuts, berry distribution is patchy, but berry production in these patches is exceptionally high. My aim was to model fine-scale temporal variation in berry production in the first years after forest cutting and determine whether bears adjust their space according to forage on clearcuts where berries are abundant. Using plot surveys on clearcuts in south-central Sweden, I collected bilberries (Vaccinium myrtillus) and lingonberries (Vaccinium vitis-idea) from 935 plots and found a nonlinear temporal dynamic of berry presence and abundance following a clearcutting procedure. On young clearcuts, berry production was depressed, it then peaked on clearcuts after around 8 years, and dropped again in later stages of succession. Additionally, bilberry and lingonberry abundance was greater on steeper slopes, with a linear relationship for bilberry and a non-linear relationship for lingonberry, which had a slight decrease at very steep slopes. I found that bears adapted to spatial and temporal dynamics of berry production by selecting for clearcuts of high bilberry presence and especially abundance. This trend was not observed in selection for lingonberry, most likely due to the smaller size of lingonberries and wider availably of bilberries in the year of study. Selection for clearcuts overall was low, with only around 10% of all recorded bear GPS positions being on clearcuts. This is potentially due to perceived hunting risk on open clearcuts and high availability of bilberries also in mature forest. Overall, clearcutting as a method of commercial harvesting of forest landscapes was found to have significant effects on berry production on clearcuts and bears adjusted their space to forage on patches with a high abundance of bilberries.